ISYARAT SOSIAL EKONOMI DALAM PEMBENTUKAN ENTITAS AGRIBISNIS KEMITRAAN PADA STRUKTUR SOSIAL KEMASYARAKATAN HETEROGEN - Serly Novita Sari; Fachrurrozie Sjarkowi; Mirza Antoni (Jurnal Bakti Agribisnis, 2017)
The objectives of this research are to: 1) identify the farmer's total income of pre-plasma in establishing agribusiness partnership entity, 2) Identify the conditions of peasant social capital as supporting efforts to establish a partnership of agribusiness entity, 3) analyze the comparation of total income between pre-plasma farmer's income and post-plasma income expectation in establishing agribusiness partnership entity, 4) Identify the response of the community in establishing partnerships agribusiness entities. The research result showed that income of farmer’s are relatively low. The conditions of peasant social capital in the village of Karang Endah and Tanjung Agung quite adequate. Farmer's income of pre-plasma (slab) is smaller than the farmers' income expectations of post-plasma (palm oil). The response of the community in establishing agribusiness partnership entity in the village of Karang Endah and Tanjung Agung was agreed, it means agribusiness investment partnerships will be easily occurred. Based on the results of those research in the village of Karang Endah and Tanjung Agung, we can conclude that Ho points 0.1 was accepted. It means if the farmer's rubber income of pre-plasma is smaller than the income of farmer's expectations of post-plasma and the conditions social capital is adequate, so the establishment of agribusiness entities will be easily occurred.